Simulação da produtividade de cana-de-açúcar (Saccharum officinarum L.) na região nordeste do Brasil, utilizando o modelo dssat - Gomes, Anthony Wellignton Almeida [UNESP]; Saad, Joáo Carlos Cury [UNESP]; Barros, Allan Cunha (My University, 2014)
The objective of this study was to simulate the potential stem and sugar yield of sugar cane (Saccharum officinarum L.) in the Northeastern Brazil (Petrolina-PE and Teresina-PI) and analyze 4 varieties in different planting seasons in two environments: irrigated and rainfed cultivars. The model of simulation was DSSAT/CANEGRO (Decision Support System for Agrotechnology Transfer) and the four sugar cane varieties were as follows: RB86 7515, CTC 4, CTC 7 and CTC 20 (all in 1.5 year cycle). Analysis of variance was performed on the results and means were compared using the Tukey test with probability level at 5%. March is the recommended month for planting in Teresina, PI. In Petrolina, PE, rainfed planting is not advisable because of the extended water deficit all year long. In an irrigated environment, no difference was found concerning stem yield as a function of planting season, for all varieties in the study regions. The stem and sugar yields were always higher in irrigated environment as compared with those in rainfed environment in all municipalities and study varieties. The simulation model provided good estimate of stem and sugar yields as compared with experimental data in Teresina, PI.
Simulation of sugar cane (saccharum officinarum l.) productivity in the northeastern brazil by the dssat model
Keywords: Irrigation; Modeling; Sugar; Yield